Defect healing via a gradient cooling strategy for efficient all-inorganic perovskite solar cells. Issue 11 (25th February 2022) - Lv, Jiani; Zhao, Wenning; Li, Wenhui; Yu, Jiatao; Zhang, Mingzhe; Han, Xiuxun; Tanaka, Tooru
Abstract : Structural defects in all-inorganic perovskite films can be partially healed via a gradient cooling strategy. Abstract : All-inorganic perovskites have drawn much attention because of their remarkable thermal stability. Nevertheless, their power conversion efficiencies (PCEs) are still limited by defect induced non-radiative recombination. In this contribution, we demonstrate a gradient cooling process to cool down the annealed perovskite films. As compared to the conventional cooling process, the structural defects are partially healed in the gradient cooling process, which is confirmed by improved crystallinity and reduced defect density. As a result, charge carrier transport in the perovskite film and at interfaces is evidenced to be enhanced. Benefitting from reduced defect density, thicker all-inorganic perovskite films without a dopant/additive achieve a champion PCE of 13.07% in carbon electrode based solar cells. This work provides a simple yet effective approach to further minimize the defect density in all-inorganic perovskites.